Percepções de alunos com necessidades educacionais especiais sobre o ensino da matemática nos anos iniciais - PRESTES, Tainá Pereira (2020)
This academic research aims to understand the perceptions of mathematics teaching of students with special educational needs in the early years, from the Theory of Development of Henri Wallon. Using the theoretical and methodological foundations of Discursive Textual Analysis, the study was carried out in a class of the 3rd year of elementary school, belonging to the state network of the municipality of Belém / PA, where we carried out the activity with three students with SEN. To reach the proposed goal, the study was organized in three stages. In the first one, we realized the aspects concerning the practice of the regent teacher. In the second stage, we applied a semistructured interview with the three participants of the research regarding the perceptions they present about the teaching of mathematics. In the third one, we performed the analysis of the data with the aforementioned analysis methodology. The study found that the comprehension of the levels of development, singularity and social contexts of each student is of great value for the development of didactic strategies that aim at the real learning of the pupil, not only in the teaching of mathematics and for students with special educational needs but for the pupil as a whole.